Diverse Heat Tolerance of the Yeast Symbionts of Platycerus Stag Beetles in Japan - Zhu, Xue-Jiao; Zhang, Sheng-Nan; Watanabe, Kana; Kawakami, Kako; Kubota, Noriko; Takagi, Etsuro; Tanahashi, Masahiko; Wen, Xiu-Jun; Kubota, Kôhei (Frontiers in Microbiology, 2022)
The genus Platycerus (Coleoptera: Lucanidae) is a small stag beetle group, which is adapted to cool-temperate deciduous broad-leaved forests in East Asia. Ten Platycerus species in Japan form a monophyletic clade endemic to Japan and inhabit species-specific climatic zones. They are reported to have co-evolutionary associations with their yeast symbionts of the genus Sheffersomyces based on host COI and yeast IGS phylogenies. Here we examined the heat tolerances of the yeast colonies isolated from the mycangia of 37 females belonging ten Japanese Platycerus species. The upper limits of growth and survival temperatures of each colony were decided by cultivating it at ten temperature levels between 17.5ºC and 40ºC. Although both temperatures varied during 25.0ºC to 31.25ºC, the maximum survival temperatures were a little higher than the maximum growth temperatures in 16 colonies. Pearson’s correlations between these temperatures and environmental factors (elevation and 19 bioclimatic variables from Worldclim database) of host beetle collection sites were calculated. These temperatures were significantly correlated with elevation negatively, the maximum temperature of the warmest month (Bio5) positively, and some precipitative variables, especially in the warm season (Bio12, 13, 16, 18) negatively. Sympatric Platycerus kawadai and P. albisomni share the same lineage of yeast symbionts that exhibit the same heat tolerance, but the elevational lower range limit of P. kawadai is higher than that of P. albisomni. Based on the field survey in their sympatric site, the maximum temperature of host wood of P. kawadai larvae is higher about 2–3ºC than that of P. albisomni larvae in the summer, which may restrict the elevational range of P. kawadai to higher area. In conclusion, it is suggested that the heat tolerance of yeast symbionts restricts the habitat range of their host Platycerus species or/and that the environmental condition that host Platycerus species prefers affect the heat tolerance of its yeast symbionts.